Designed plant communities for challenging urban environments in southern Finland : based on the German mixed planting system - Seppänen, Sara (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2019)
Traditional perennial borders require a lot of maintenance and are therefore not so common in public areas in Finland. There is a need for low-maintenance perennial plantings that can tolerate the dry conditions in urban areas. Especially areas close to traffic, such as the middle of roundabouts and traffic islands need easily manageable vegetation and they are therefore normally covered in grass or mass plantings of shrubs. Well-designed plant communities require less maintenance than lawns and are more biodiverse and visually interesting than mass plantings. In the 1990s a Mixed Planting system was developed in Germany, with perennial mixes for public plantings and since then over 30 different mixes have been trialled and tested. The mixes were created for a specific habitat and can be used in different areas with that same habitat. However, the German climate is different from the Finnish and the mixes cannot therefore be used as they are. The Finnish climate is looked into with a focus on urban climate to get an understanding of what is required of a plant to survive in these conditions.